PENGARUH PADAT TEBAR SELTER RUMPUT LAUT (Gracillaria sp) TERHADAP PERTUMBUHAN DAN SINTASAN RAJUNGAN (Portunus pelagicus) DI TAMBAK - Suharyanto Suharyanto; Suwardi Tahe; Sulaeman Sulaeman (Universitas Gadjah Mada, 2008)
The aim of this experiment was to find out the suitable stocking density of sea weed as shelter to growth and survival rate of swimming crabs (Portunus pelagicus) reared in brackishwater ponds. The research was conducted in nine brackishwater ponds with the dimension of 250 m2 for 120 days. The treatments different stocking density of sea weed (Gracillaria sp.) as shelter were applied, namely A: 500 kg/ha, B: 750 kg/ha, and C: 1000 kg/ha, with three replicates, respectively. Crablet 9th with carapace width 5,2 + 0.2 mm and body weight 0.04 + 0.02 g were introduced into each experimental ponds with density of 3 individu/m2. The crabs were fed with trash fish 15% of body weight in the first month, and then decreased to 5% in following month, twice a day. The experiments were design as complately randomized design. The result showed that the shelter were significantly increased to the survival rate and yield of swimming crabs (P<0.05), but not to the growth of charapace width and body weight. The best of survival rate and yield was obtained on the density of shelter at sum 1000 kg/ha.